Educação ambiental e aprendizagem dialógica: possibilidades e limites para a transformação da escola e seu entorno - Ribeiro, Caroline Lins (Universidade Federal de São Carlos, 2009)
The research focuses on the construction of knowledge about teaching practices in environmental education, linked to the social perspective, transformative, democratic and dialogical. We have the participation of two teachers of the Collective Environmental Educator of Campinas (Coeduc), part of the National Training of Environmental Educators (Profea) guided by the guidelines of the national environmental education. We traveled paths with teachers identifying the obstacles in their practices and ways of overcoming these, towards the school we want. We conducted our research with the guidance of the communicative and qualitative methodology. We approach the critical method of communication, who guided us on the instruments for data collection and analysis procedures, ensuring the intersubjective dialogue and reflection, enabling deep learning, processing and discussion about the capabilities of interpretation of reality made by the subjects who live . It will explain that the school needs to ensure access for people demanding activities and practices in context and reflective about the environmental problems of today. Thinking of overcoming inequalities, strengthened and generated by the mainstream in the information society, we choose the critical environmental education and dialogic learning, elucidated by authors who bet on the contribution of education for social transformation. Therefore, we raised a record on the information society and the environmental movement, environmental education and its context. We point out the theoretical underpinnings of the dialogic learning, explaining the communicative action Habermas, Freire and dialogical in learning and development in Vygotsky to support our research. Before the analysis with the teachers realize that the power of collective participation and the possible changes in the school environment and beyond. An instrument is a communicative action, with proposals to transform reality, linked to contexts, cultures and personal experiences, especially the intersubjective interactions. In this sense, the critical environmental education built as public policy is marked by great challenges also faced by social movements, education, involving different people and institutions who strive for a school and a society more just, equitable and environmentally sustainable.
Keywords: Educação ambiental; Aprendizagem dialógica; Coletivos educadores; Escola democrática; Participação; Teacher collective; Critical environmental education; Dialogical learning; Democratic school; Participation; CIENCIAS HUMANAS::EDUCACAO